Analisis Karakteristik Aplikasi Kamus Arab-Indonesia Karya Tim Ristek Muslim - Maulida Almas Fadhilah (Alsina : Journal of Arabic Studies, 2021)
This study is driven by the fact that Arabic is often seen as a complex language to master in many Indonesian schools and madrasas. This educational issue has resulted in various efforts to facilitate learning using meaningful innovations. The researchers created online and offline programs, including an Arabic-Indonesian dictionary built for Android. The current research tries to ascertain the applicability of the Arabic-Indonesian dictionary. This study is a literature review study using a descriptive qualitative approach. The developers (Surabaya Muslim Research and Technology Team) created the application in 2012 and used a variety of secondary sources, including articles, journals, and pertinent documents. The Arabic-Indonesian Dictionary is an Android-based Arabic-Indonesian dictionary application capable of translating Indonesian to Arabic and vice versa. This application database has 154,644 Arabic vocabularies. The dictionaries contained in this application include the Arabic-Indonesian Dictionary, Munawwir Dictionary, Muʿjam al-ʿArab, Muʿjam al-Muʿāṣirāh, Lisān al-ʿArabic, Muʿjam al-Ghanī, and the Al-Qur'an Dictionary. This dictionary can be used as an Arabic learning media.